Discovery-Inquiry Learning Model in Delivering Living Creature Classification Material for High School/Equivalent Schools - Priyanti, Novie Ary; Pratama, Raditya; Puspaningsih, Eunike Sri; Rahmania, Ika; Niswatus Sufiyah; Liza Choirun Nisa'; M. Zainul Muttaqin; Sarlotha Selan (International Journal of Sustainable English Language, Education, and Science, 2024)
This research provides an understanding of why the Discovery-Inquiry learning method as a means to deliver the classification of living things. This research uses a descriptive qualitative approach, descriptive by conveying clearly what is meant by discovery-inquiry and why it is appropriate when implemented in the material of the diversity of living things. Education is a planned and conscious effort to create a learning atmosphere and learning process in which students actively develop their potential, discovery-inquiry is an option in its delivery. Discovery-inquiry is a learning process where a concept is not presented in its final form, but students must organize their own learning by finding out these concepts. Meanwhile, the classification of living things classifies living things based on certain characteristics. So, of course it is very related to the discovery-inquiry method which requires students to play a greater role than the teacher by finding and ensuring the object under study whether it is in accordance with the theory or finding something new.